Dari Warisan Budaya Menuju Firman Tuhan : Strategi Pembinaan Rohani dalam Transformasi Praktik Penguburan di Desa Terusan, Kabupaten Ketapang, Kalbar, Berdasarkan 1 Timotius 6:7 (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
This PKM examines the transformation of traditional burial practices in Terusan Village, Ketapang Regency, West Kalimantan, in light of 1 Timothy 6:7. The local community has a tradition of accompanying and placing all the personal belongings of the deceased on the grave as a form of respect and the belief that the deceased's spirit needs these items to prevent them from returning angry. This belief is reinforced by the community's past spiritual experiences, including the testimony of traditional leaders about dreams in which the deceased's spirit asks for their belongings. Using a theological and anthropological approach, this PKM assesses this tradition in relation to the biblical teaching that humans bring nothing into or out of the world. Using theories from theologians and anthropologists, this PKM formulates a dialogical, inculturative, and transformative spiritual development strategy, so that local culture can be guided without experiencing rejection. This PKM concludes that changes in burial practices must be carried out with a pastoral approach that emphasizes the value of spiritual wealth, the hope of resurrection, and an understanding of death in Christ. Thus, local traditions are not erased, but are guided toward new meanings that align with God's Word, leading the community from cultural heritage to genuine spiritual transformation.